Radio frequency peak and average power density from mobile base stations in Ekiti State, Nigeria - Ilesanmi B. Oluwafemi; Adedeji M. Faluru; Tayo D. Obasanyo (Institute of Advanced Engineering and Science, 2021)
The ever-increasing number of mobile telecommunication base station as a result of increasing demand for broadband applications has raised a growing concern and worry over the health implications and safety of the radiations from these base stations by the resident of Ekiti State and Nigeria in Nigeria. Measurement of radio frequency was conducted in this research in order to study the electromagnetic field radiation level in Ekiti State Nigeria. Investigation was conducted with the four available mobile operators with the three sub-frequency band viz 900 MHz, 1800 MHz and 2100 MHz. The power density of radio frequency radiation was estimated through measurement with the aid of A 3-Axis RF Radiation Strength Meter TM-196 and Handheld Spectrum Analyzer Model NA-773, 144/430. The peak and average power density was computed using the method of theoretical calculation and the safety distance from the antennas were estimated. The measured and the calculated values were compared with the international commission on non-ionizing radiation protection (ICNIRP) standard for public and occupational exposure level. Results show that the radiations from the base stations adheres to the standard provided by ICNIRP